(untitled) (Research, Society and Development, 2021)
Inflammation is the body’s response to harmful stimuli such as infections, trauma, or injury. The inflammatory cascade can lead to the development of numerous diseases, and the current drug-therapeutic intervention consists of the use of corticosteroids and non-steroidal anti-inflammatory drugs. However, the use of these is associated with several serious side effects, so it is necessary to search for new alternatives that can minimize this effect. In this prospecting, the objective was to conduct a study on biological activities already described for vanillic acid, with special emphasis on its semi-synthetic derivative of isopropyl vanylate as an anti-inflammatory agent. For this, information was obtained on patent documents based on the INPI, USPTO and EPO databases, using the keywords: vanillic acid, anti-inflammatory agents, isopropyl vanylate, always used in the search field related to the summary of works. As results obtained in the present technological prospection study, it was found that in the international patent databases the documents related to the theme were very scarce and some had a higher number of patents, on vanillic acid, few refer to its anti- inflammatory, and no documents were found on the use of isopropyl vanillate as an anti-inflammatory agent, reinforcing the innovative character of research involving its use in this technology.